Digital transformation solutions in human resource management at Sen interior decoration joint stock company – Binh Duong branch - Ngo, Văn Hà (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2023)
Digital transformation in human resource management will bring many benefits to businesses. However, businesses have not yet found an optimal solution in implementing digital transformation into human resource management activities. At Sen interior Decoration joint stock company - Binh Duong branch, human resource management with costs and resources requires a lot of investment but the efficiency is not high. This research objective is to find the best solution to implement digital transformation into human resource management. The research method is qualitative analysis, combining expert interview method, descriptive statistics method and comparative method to achieve the goal. The research has pointed out the achievements as well as the limitations and difficulties in the practice of digital transformation activities in human resource management at the Company. Since there, the author proposes digital transformation solutions in human resource management at Sen interior Decoration joint stock company - Binh Duong Branch.